Editorial - Michael Owen (Brock Education: a Journal of Educational Research and Practice)
This issue represents my first as Editor-in-Chief of Brock Education. It is an honour to fill this role at a time in which the academic world is in great turmoil, in Canada and across the globe. Our daily newsfeeds are filled with stories of direct and indirect challenges to academic freedom, freedom of speech, EDID (Equity, Diversity, Inclusion, and Decolonization), student mobility, funding of institutions, and intra- and extramural research. As scholars, we need to be conscious of the noise of those who seek to undermine education and hinder scholarship and knowledge mobilization. We need to focus on those aspects of our lives as teachers, researchers, and leaders that will allow us to reinforce the foundations of learning and teaching across the lifespan while maintaining our own well-being.